Colossians and Philemon - Beale, G. K. (Gregory K.), 1949- (Grand Rapids Baker Academic, 2019)
"A leading New Testament scholar offers a substantive evangelical commentary on Colossians and Philemon in the award-winning BECNT series"--
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries